2021
DOI: 10.1063/5.0053884
|View full text |Cite
|
Sign up to set email alerts
|

Observation of spatially resolved Rashba states on the surface of CH3NH3PbBr3 single crystals

Abstract: Hybrid organic-inorganic perovskites (HOIPs) are prime candidates for studying Rashba effects due to the heavy metal and halogen atoms in their crystal structure coupled with predicted inversion symmetry breaking. Nevertheless, observation of the Rashba effect in cubic CH3NH3PbBr3 single crystals that possess bulk inversion symmetry is the subject of extensive debate due to the lack of conclusive experiments and theoretical explanations. Here, we provide experimental evidence that Rashba state in cubic CH3NH3P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…In summary, by combining optical spectroscopy measurements with first-principles electronic structure calculations of the interfaces between MAPI and PbI 2 , we provided microscopic insights into the role of excess PbI 2 in PSCs. Consistent with previous investigations, our results point to the key role of surface terminations and interfaces in determining the properties of hybrid perovskites. , We found that excess PbI 2 on MAPI does not just provide passivation of the MAPI surface. Depending on whether the metal or the halide terminate the PbI 2 surface, different band alignments with the MAPI are possible and, importantly, different concentrations of Frenkel defects may be present, which in turn affect the electronic structure of the interface.…”
supporting
confidence: 92%
“…In summary, by combining optical spectroscopy measurements with first-principles electronic structure calculations of the interfaces between MAPI and PbI 2 , we provided microscopic insights into the role of excess PbI 2 in PSCs. Consistent with previous investigations, our results point to the key role of surface terminations and interfaces in determining the properties of hybrid perovskites. , We found that excess PbI 2 on MAPI does not just provide passivation of the MAPI surface. Depending on whether the metal or the halide terminate the PbI 2 surface, different band alignments with the MAPI are possible and, importantly, different concentrations of Frenkel defects may be present, which in turn affect the electronic structure of the interface.…”
supporting
confidence: 92%
“…The spin polarization relaxation time of hybrid metal-halide perovskite materials is shorter than III–V systems, reaching the picosecond range at room temperature and nanosecond range at low temperatures. To the best of our knowledge, there are no reports investigating the spin polarization dynamics of chiral lead-free perovskites. However, we believe that chiral perovskites should offer a high degree of spin polarization and long spin polarization relaxation times due to the unique combination of advantageous properties provided by chiral materials and lead-free HOIPs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to spin-orbit interaction and lack of inversion-symmetry of the crystal potential, Rashba band splitting has been observed in perovskites. 29 Although the crystal bulk of our MAPbBr 3 perovskite is a centrosymmetrical structure, 30 symmetry breaking can still occur for the Rashba splitting effect in the polycrystalline thin film based on the following considerations: (1) symmetry breaking forms at the perovskite interface due to the asymmetric perovskite/ambient layout, as evidenced by many different experimental characterizations based on the MAPbBr 3 single crystal, e.g., angleresolved photoemission (ARPES) results 31 and circular photogalvanic effect together with spatially resolved photoinduced inverse spin Hall effect measurements; 32 (2) the PbBr 6 octahedral thermal polar distortions at elevated temperatures can lead to a dynamical Rashba splitting effect; 33 (3) the strain inside the perovskite thin film can cause PbBr 6 octahedral distortion, increasing the possibility of the Rashba splitting effect. 34 Such unique band structure enables the two-photon absorption process that excites the electrons into a high energy band with opposite spins following the selection rule DJ = AE2, while the one-photon absorption only occurs between two bands with the same spin (DJ = AE1).…”
Section: Efficient Carrier Accumulation For Two-photon Upconversion Asementioning
confidence: 99%